Gendered Meanings in AI-Mediated Customer Communication: Female Chatbots in Banking and Telecommunications - Intan Fitranisa; Dimas Ramadhiansyah (FAKULTAS DAKWAH UIN SALATIGA, 2026)
AI-mediated customer communication has become increasingly prevalent in service industries, particularly through the adoption of chatbots as digital communication agents between organizations and consumers. Beyond their functional role in delivering information and assistance, chatbots often incorporate gendered identities that shape how users interpret and engage with digital interactions. In Indonesia, banking and telecommunications companies widely employ female-coded chatbots as part of their customer communication strategies. This study explores consumers’ perceptions of female chatbots and examines how gendered meanings are negotiated within AI-mediated customer communication. Using a qualitative exploratory approach, in-depth interviews were conducted with consumers who had experience interacting with female chatbots in the banking and telecommunications sectors. The findings reveal that participants generally perceive female chatbots as extensions of frontline customer service communication in digital environments. While participants demonstrated varying interpretations of female chatbot representations, they frequently associated these chatbots with characteristics such as friendliness, patience, and helpfulness. The findings also suggest that the predominance of female-coded chatbots may contribute to the normalization and potential reinforcement of gender stereotypes linking women to service-oriented and emotional labor roles. This study contributes to communication scholarship by highlighting how gendered meanings are embedded, interpreted, and negotiated within AI-mediated customer communication.